Hydrous components of grossular-andradite garnets from Thailand: Thermal stability and exchange kinetics - Bongkot Phichaikamjornwut (2018)
Grossular-andradite garnet from three localities of skarn deposits in Thailand were studied by FTIR spectroscopy to investigate the occurrence of hydrous components. Characteristic OH absorption bands were present in the spectra of all samples, with intensities corresponding to OH concentrations in the range 0.01-0.34 wt% H 2O. The distribution of absorption bands vary relatively strongly among samples, partly correlated with sample composition. Fourteen samples were chosen for step-wise heating experiments at 700-900 °C in air or H 2 atmosphere, with subsequent acquisition of IR spectra. Diffusion coefficients for the dehydration and rehydration reactions were obtained by fitting the changing OH concentrations calculated from the absorbance of the individual OH bands. The results indicate that the rehydration reaction is normally faster than the dehydration reaction. As previously reported, individual bands show a somewhat different behaviour during the experimental heat treatments, which indicates that several different types of OH defects occur in these grossular-andradite solid-solutions. Mössbauer spectra acquired before and after heat treatments show that hydrogen exchange occurs without charge compensation by the Fe redox state. © 2011 E. Schweizerbart'sche Verlagsbuchhandlung.